The Effect of Self Regulated Strategy Development on Students’ Skill to Write Persuasive Text - Dewi Sartika; Rachmanita Rachmanita (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2017)
Writing is one of the four skills taught in the school which is used as communication in daily life. It is considered as a difficult subject by the eleventh grade of the senior high school students because of the limitation of the time provided and some aspects of language to be considered. Therefore, the purpose of this study was to find out whether or not there was a significant difference in students’ writing achievement of persuasive text between the students who were taught by using Self-Regulated Strategy Development and that of those who were not. By conducting a quasi-experimental investigation at senior high school level in South Sumatera, Indonesia, two classes consisting of thirty students in each class at SMA Negeri 1 Kandis were chosen as the samples by using purposive sampling method. To analyze the data, the t-test was used. The result findings showed that t-obtained (3.29) was higher than t-table (2.0017) at the significance level of p-value was lower than 0.05. It indicated that there was a significant difference in students’ writing achievement of writing persuasive text between the students who were taught by using Self-Regulated Strategy Development and that of those who were not. The students who were taught by using Self-Regulated Strategy Development had better improvement in their writing persuasive text because the students could write the persuasive text well based on the Self-Regulated Strategy Development which applied POW (pick, organize, write)  and TREE  (topic, reasons, explanation, ending).